Pendekatan Sufistik dalam Pendidikan Islam (Telaah Pemikiran Hamka) - Muhamad Rifai Subhi (Edukasia Islamika : Jurnal Pendidikan Islam, 2016)
The background of this research is the same objective of Hamka’s concept relatedto modern tasawuf with the concept of Islamic education which aims to createqualified human being by balancing the physical and spiritual life. This study useslibrary research method through intellectual biography approach and content analysis in analyzing the data. Research result shows that according to Hamka, there are two main dimensions which appears from human beings; they are dimension of vertical submission to God and dimension of horizontal dialectic with the surrounding societies. Therefore, in order to realize the objective of Islamic education, it is necessary to provide Islamic learning material which can develop students’ potential in expressing their competence.